Sosialisasi Kreativitas, Komunikasi, serta Sadar Lingkungan: Pendampingan Siswa dalam Upaya Meningkatkan Kreativitas dan Public Speaking - Prabowo, Budi; Haque, Annisa Mutiara Salma; Josilina, Grecila Naftali; Tanzaga, Daivan Putra; Putra, Victor Pramudita (Pusat Riset dan Inovasi Nasional, 2024)
Education plays an important role in student development, especially in developing effective communication skills or public speaking. This community service aims to improve the creativity and public speaking skills of students at SDN Sumput, Sidoarjo, through socialization activities for making flower pots from plastic bottle waste. The main problems identified were the lack of self-confidence and public speaking skills among grade 5 students. Lack of interest and motivation as well as fear of public speaking hinder the learning process. The implementation method includes environmental observation, problem identification, activity coordination, and implementation of socialization and mentoring. This socialization was carried out on July 29, 2024, involving 15 students divided into 3 groups. Students were accompanied by KKN students in the process of recycling plastic bottles into flower pots and were trained in public speaking through presentations of their work. The results of this activity show that students not only improve their creative and public speaking skills, but also understand the importance of waste management and environmental awareness.